In Silico evaluation of phytoconstituents from Carica Papaya and its anti-hyperglycemic activities on high sucrose-induced oxidative stress in Drosophila melanogaster - Omotade I. Oloyede; Seun J. Ibrahim; Scholastica O. Anadozie; Erdi C. Aytar; Oluwole B. Akawa; Isaac A. Adu; Oluwadunsin S. Omodaratan; Olabisi T. Obafemi; Olusola B. Adewale (Scientific Reports)
Abstract Oxidative stress plays a key role in the development of metabolic disorders, such as diabetes. This study investigated the phytoconstituents present in Carica papaya (AECP) using an in silico model, and its anti-hyperglycemic activities on high sucrose-induced oxidative stress in Drosophila melanogaster. In silico molecular docking was performed to analyze the binding potential of AECP’s bioactive compounds to key diabetes targets. Flies were fed a diet containing 30% sucrose to induce oxidative stress, followed by administration of AECP at doses of 50 and 100 mg/kg for five days. Biochemical assays assessed were glucose, total thiols, catalase, glutathione S-transferase (GST), and nitric oxide. In silico analysis revealed that carpaine, myricetin 3-rhamnoside, orientin 7-O-rhamnoside, and quercetin in AECP exhibited strong binding potential to key diabetes targets (alpha-amylase, beta-glucosidase, dipeptidyl peptidase 4, PPARG, and SGLT-2)). In fruit flies, sucrose-diet significantly (p < 0.05) reduced total thiol level, and catalase and GST activities while increasing glucose and nitric oxide levels. The AECP in a dose-dependent manner significantly (p < 0.05) reversed these changes, demonstrating its antioxidant and possible anti-hyperglycemic properties. These findings suggest that AECP may be a potential therapeutic agent for mitigating oxidative stress and supports its potential use in managing diabetes.